Peran Literasi Keuangan dalam Memoderasi Pengaruh Fear of Missing Out dan Diskon E-Commerce terhadap Perilaku Konsumtif Belanja Online di Shopee - Rhida Arsy Farah Diba; Dyah Ratnawati (Jurnal Riset Akuntansi, 2026)
The purpose of this study is to examine how Fear of Missing Out (FoMO) and e-commerce discounts influence online shopping behavior on Shopee. Additionally, this study investigates the role of financial literacy as a moderator variable. A quantitative method was used in this study. The study population consisted of active undergraduate students in the Faculty of Economics and Business at UPN “Veteran” in East Java. Purposive sampling was used to collect the research sample, which consisted of 98 respondents. SmartPLS 4.0 was used to analyze the SEM-PLS model after data was collected via an online questionnaire using a Likert scale. The results indicate that FoMO has a positive and significant influence on consumer behavior. E-commerce discounts also have a positive and significant influence on consumptive behavior, and this is the most dominant variable. However, FoMO and e-commerce discounts were not proven to be able to control consumptive behavior. These findings indicate that psychological drives and promotional appeal are more dominant than financial literacy in influencing students’ consumptive behavior.